Methods of testing refractory materials Part 1B. Basic refractory materials (BSI, 1967)
Refractory materials, Refractories, Testing, Basic refractories, Refractory bricks, Shaped refractories, Unshaped refractories, Sampling methods, Porosity measurement, Density measurement, Volume measurement, Thermal expansion, Heating tests, Chemical-resistance tests, Thermal testing, Fracture, Hydration, Water content determination, Measures (containers), Determination of content, Concentration (chemical)